Prevalência e frequência de sintomas osteomusculares em docentes da coordenação de eletrônica da UTFPR - Campus Pato Branco - Weschenfelder, Francielle Zancanaro (2011)
This research analyzed the prevalence and frequency of musculoskeletal symptoms in teachers in the electronic group at Federal Technological University of Paraná – Pato Branco Campus. The study was configured as field research, with a descriptive and exploratory character composed by a cross-sectional study. They were applied as research instruments, an uphold questionnaire composed of questions about socio-demographic, occupational and physical condition, and in sequence, a basic questionnaire, specific for this study, entitled Nordic Questionnaire. The results show that 89% of the teachers had already had some musculoskeletal symptoms. The age group with highest incidence was between 30 - 39 years, with a medium age of 33.9 years. The body areas with the most complain were the neck (61%), upper back (61%) and shoulders (44%) all of them with a moderate degree of severity. Analyzing the most affected body areas in the last 7 days they were found the shoulders (28%), followed by the neck (22%) and wrist (22%). When analyzing a period of 12 months it is realized that the most affected areas were shoulders (33%), upper back (33%) and neck (28%). Discussing the frequency of symptoms, the highest levels were present in the neck, shoulder and ankle/foot, where the pain always exists. The conclusion is that the musculoskeletal symptoms affect a young population of teachers with an average of 8.8 years in the occupation. The most affected body areas are the upper extremities (neck, upper back, shoulders) revealing frequent musculoskeletal symptoms with moderate degree of severity.